Local Organization : Confronting Contradition in a Smallholding District of Kenya - Mackenzie, Fiona (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1987)
The objective in this paper is to link changes in productive/reproductive relations between women and men to changes in mode of local organization. It is argued that women's ability to organize local, non-kin networks at the extrahousehold level in Murang'a District, Kenya has, through time, served as a countertension to male solidarity. Evidence is presented to indicate how women have formed effective social bonds on the basis of spatial contiguity, a pattern that has been replicated through time, albeit altering as necessitated by changes in productive mode.